The real exchange rate and economic growth: Revisiting the case using external instruments. (May 2017) - Habib, Maurizio Michael; Mileva, Elitza; Stracca, Livio
Abstract: We investigate the impact of movements in the real exchange rate on economic growth based on five-year average data for a panel of over 150 countries in the post Bretton Woods period. Unlike previous literature, we use external instruments to deal with possible reverse causality from growth to the real exchange rate. Our country-specific instruments are (i) global capital flows interacted with individual countries' financial openness and (ii) the growth rate of official reserves. We find that a real appreciation (depreciation) reduces (raises) significantly annual real GDP growth, more than in previous estimates in the literature. However, our results confirm this effect only for developing countries and for pegs.